Estafet and Collaborative Writing with Tutorial Video to Increase Students’ Understanding of Procedure Text - Firmansyah, Muchammad Sofyan; Fauzi, Arief Zul; Romadhon, Syaefani Arif (LPPM Universitas Pancasakti Tegal, 2020)
In this study, researchers examined how the implementation of the ESCO method combined with video material media in improving the ability to write English procedure text. This study belongs to Class Action Research. The data analysis method used descriptive quantitative method. The respondents in this study were 44 first-year students of the Applied Bachelor of Public Sector Accounting department of Polytechnic Harapan Bersama who were gathered in one class and given the same treatment. The data were collected using a pretest-posttest assessment and a questionnaire. The data obtained in the form of a pre-test and post-test were analysed to see if there was an increase in the student's ability to write procedural texts. The analysis of the pre-test and post-test scores was combined with the students’ questionnaire which contained students’ opinions regarding the implementation of the ESCO method as a learning method. The results of this study indicated that there is an increase in the student's ability to write procedural texts in English as an improvement between their pre-test and post-test scores.